Allergies and Eosinophilic Esophagitis– Current Updates for the Pediatric Gastroenterologist - Williamson, Prerana (Curr Gastroenterol Rep, 2019)
PURPOSE OF REVIEW: The purpose of this article is to review recent developments demonstrating the role of allergies, the utility of allergy testing, and the role of the allergist in eosinophilic esophagitis (EoE) management. RECENT FINDINGS: The majority of patients with EoE have concurrent atopic disorders including food anaphylaxis, asthma, allergic rhinitis, and eczema. An atopic population likely is at greater risk for EoE. Delayed type hypersensitivity to food antigens is the most common pathogenic mechanism. Aeroallergens and pollen-food cross reactivity also can trigger EoE. Th2 cell mediated adaptive and innate immunity in response to epithelial damage occurs via IL-13, −4 producing T cells and innate lymphoid cells. While IgE testing for foods is insufficient to build an elimination diet, IgE-mediated allergy may play a role in EoE severity and clinical course. SUMMARY: There is strong evidence that Th2 immunity drives EoE. Optimal EoE management should include elucidating and managing EoE triggers and concurrent atopic diatheses.